2008
DOI: 10.1016/j.cellbi.2008.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Cell type dependent endocytic internalization of ErbB2 with an artificial peptide ligand that binds to ErbB2

Abstract: ErbB2, which is a member of the epidermal growth factor (erbB) receptor family, is frequently overexpressed in breast and ovarian cancers. Antibody and small molecule anti-tyrosine kinase inhibitors have been developed for targeted therapies for cancers overexpressing erbB2. Internalization and downregulation of erbB2, which is induced by a ligand, may be important for efficacious therapeutic effects. However, ligand-dependent erbB2 internalization has not been well characterized. Here we investigated the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 41 publications
6
27
0
Order By: Relevance
“…It was not possible to evaluate the effect of treatment with trastuzumab in vivo on the uptake of 111 In-DTPApertuzumab in SKBr-3 cells, because these cells are poorly tumorigenic in athymic mice. The differences between MDA-MB-361 and SKBr-3 cells in HER2 downregulation caused by trastuzumab are consistent with earlier reports that HER2 on SKBr-3 cells are internalization-impaired (17,18). Hashizume et al (17) proposed that coexistent HER3 on SKBr-3 cells may impair HER2 internalization; however, in our study, radioligand binding assays with 111 In-DTPApertuzumab and flow cytometry and immunofluorescence confocal microscopy demonstrated that HER2 on MDA-MB-361 cells was downregulated by trastuzumab, despite the fact that these cells have HER3 expression similar to that of SKBr-3 cells (19).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It was not possible to evaluate the effect of treatment with trastuzumab in vivo on the uptake of 111 In-DTPApertuzumab in SKBr-3 cells, because these cells are poorly tumorigenic in athymic mice. The differences between MDA-MB-361 and SKBr-3 cells in HER2 downregulation caused by trastuzumab are consistent with earlier reports that HER2 on SKBr-3 cells are internalization-impaired (17,18). Hashizume et al (17) proposed that coexistent HER3 on SKBr-3 cells may impair HER2 internalization; however, in our study, radioligand binding assays with 111 In-DTPApertuzumab and flow cytometry and immunofluorescence confocal microscopy demonstrated that HER2 on MDA-MB-361 cells was downregulated by trastuzumab, despite the fact that these cells have HER3 expression similar to that of SKBr-3 cells (19).…”
Section: Discussionsupporting
confidence: 80%
“…The differences between MDA-MB-361 and SKBr-3 cells in HER2 downregulation caused by trastuzumab are consistent with earlier reports that HER2 on SKBr-3 cells are internalization-impaired (17,18). Hashizume et al (17) proposed that coexistent HER3 on SKBr-3 cells may impair HER2 internalization; however, in our study, radioligand binding assays with 111 In-DTPApertuzumab and flow cytometry and immunofluorescence confocal microscopy demonstrated that HER2 on MDA-MB-361 cells was downregulated by trastuzumab, despite the fact that these cells have HER3 expression similar to that of SKBr-3 cells (19). Interestingly, although hIgG and rituximab caused no changes in HER2 expression levels in SKBr-3 and MDA-MB-361 cells in vitro, there was an apparent but statistically insignificant decrease in tumor uptake of 111 In- DTPA-pertuzumab mice treated with hIgG or rituximab in vivo.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, ErbB2 bound to Trastuzumab was shown to undergo multiple cycles of ErbB2 recycling and to slowly enter the lysosomes, leading to ErbB2 down-regulation (10,46). Similarly, increased endocytosis and down-regulation of surface ErbB2 has been observed with artificial peptide and aptamer ligands (47,48).…”
mentioning
confidence: 92%
“…Immunofluorescence-based internalization studies were also done on SKOV3 and MCF7 cells (27). Cells treated with immunotoxins or rGel were subjected to immunofluorescent staining with anti-rGel antibody (FITC-conjugated secondary antibody).…”
Section: Methodsmentioning
confidence: 99%